Use of Indicator Kriging to Investigate Schistosomiasis in Minas Gerais State, Brazil - Ricardo J. P. S. Guimarães; Corina C. Freitas; Luciano V. Dutra; Carlos A. Felgueiras; Sandra C. Drummond; Sandra H. C. Tibiriçá; Guilherme Oliveira; Omar S. Carvalho (Journal of Tropical Medicine)
Geographic Information Systems (GISs) are composed of useful tools to map and to model the spatial distribution of events that have geographic importance as schistosomiasis. This paper is a review of the use the indicator kriging, implemented on the Georeferenced Information Processing System (SPRING) to make inferences about the prevalence of schistosomiasis and the presence of the species of Biomphalaria, intermediate hosts of Schistosoma mansoni, in areas without this information, in the Minas Gerais State, Brazil. The results were two maps. The first one was a map of Biomphalaria species, and the second was a new map of estimated prevalence of schistosomiasis. The obtained results showed that the indicator kriging can be used to better allocate resources for study and control of schistosomiasis in areas with transmission or the possibility of disease transmission.